HealthStat: measuring the performance of the Irish public health service - Turner, Mark (Statistical and Social Inquiry Society of Ireland, 2009)
HealthStat is a tool for measuring the performance of the Irish public health service. It consists of a data collection process, the production of performance statistics in graphical dashboard format and a monthly accountability forum that invites a rotating selection of service delivery units. HealthStat ran in pilot phase throughout 2008. Performance dashboards for 29 general and regional hospitals were first published in the public domain on 23rd March 2009. HealthStat will extend to all remaining hospitals and to community health and social care services during 2009. This paper describes, from a health information perspective, the background to HealthStat, the challenges faced and the way ahead.
read before the Society April 30th, 2009
Keywords: HealthStat; Public health; Data collection; Performance indicators; 314.15